Pemanfaatan Media Sosial dalam Optimalisasi Bisnis UMKM di Gorontalo Menurut Prespektif Ekonomi Islam - Fauziah Husain; Azka Faizah Mahmud; Naura Rahida; Melis Mustapa (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to analyze the use of social media in optimizing the business of Micro, Small and Medium Enterprises (MSMEs) in Gorontalo through an Islamic economic perspective. In today's digital era, social media is one of the important tools that can increase the visibility and competitiveness of MSMEs. This type of research is qualitative this research utilizes interviews and observations at Rahida Cookies Gorontalo to dig up in-depth information about MSME business practices in Gorontalo. The results of Rahida Cookies' research, by utilizing social media for promotion, are also able to show business transparency to customers, so that customer trust can be maintained. Rahida Cookies applies these principles by ensuring that their products are not only of high quality but also meet halal criteria. They are committed to providing products that are beneficial to society and do not harm any party.From an Islamic economic perspective, the use of social media as a promotional medium can be seen as an effort to run a business efficiently, transparently and responsibly. Islamic economics emphasizes justice (adl), honesty (siddiq), and blessings in every business.